Department of Education's Student Loan Programs: Are Tax Dollars at Risk? Hearing before the Subcommittee on Criminal Justice, Drug Policy, and Human Resources of the Committee on Government Reform. House of Representatives, One Hundred Sixth Congress, First Session. - Congress of the U.S., Washington, DC. House Committee on Government Reform; Congress of the U.S., Washington, DC. House Committee on Government Reform ([Washington, D.C.] : Distributed by ERIC Clearinghouse, 1999)
This hearing was held to consider whether the student loan programs of the Department of Education place tax dollars at risk. In his opening remarks, Representative John L. Mica (Florida) pointed out that for nearly 10 years, the U.S. General Accounting Office has labeled these programs as a high risk for fraud, waste, abuse, and mismanagement. In 1998, Congress created the first Federal sector performance based organization (PBO) to bring about some reforms in student loan programs. One purpose of these hearings was to assess the PBO's progress to date. A recent report by the Inspector General's Office suggests that the Department of Education has incorrectly forgiven many loans to students who could well be paying them back, especially students who claimed to be dead when they were not. Although the default rate on student loans has dropped slightly, there were still about $20 million in default at the time of the hearing. Statements about the student loan program and the need for reform were given by Representatives Elijah E. Cummings (Maryland), Benjamin Gilman (New York), Dennis Kucinich (Ohio), and Patsy T. Mink (Hawaii). Also presenting testimony were: (1) John Berthoud, National Taxpayers Union; (2) Thomas A. Butts, National Direct Student Loan Coalition; (3) Fred J. Galloway, former loan program evaluator; (4) Steven A. McNamara, Assistant Inspector General for Audit (Department of Education); (5) Marshall S. Smith, Acting Deputy Secretary, Department of Education; and (6) Greg Woods, Chief Operating Office, Office of Student Financial Assistance Programs, Department of Education. The prepared statements of these witnesses and letters and statements submitted for the record are included. Among these, the report of the Office of the Inspector General, U.S. Department of Education is of particular interest. (SLD)
Availability: For full text: http://www.gpo.gov/congress/house or http://www.house.gov/reform.
ERIC Note: Serial No. 106-103.
May also be available online. Address as at 14/8/18
Microfiche.
Keywords: Cost Effectiveness; Debt (Financial); Educational Finance; Federal Programs; Hearings; Higher Education; Loan Default; Loan Repayment; Student Loan Programs; Taxes; Congress 106th; Legal/Legislative/Regulatory Materials